2019
DOI: 10.21203/rs.2.14499/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative transcriptomics reveal conserved impacts of rearing density on immune response of two important aquaculture species

Abstract: Background: Infectious diseases represent an important barrier to sustainable aquaculture development. Rearing density can substantially impact fish productivity, health and welfare in aquaculture, including growth rates, behaviour and, crucially, immune activity. Given the current emphasis on aquaculture diversification, stress-related indicators broadly applicable across species are needed. Results: Utilising an interspecific comparative transcriptomic (RNAseq) approach, we compared gill gene expression resp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The subsequent impact of these altered light regimes on both fish behaviour and health is now being considered. Recent studies have also found parasitic infection can alter host circadian gene expression, further complicating the relationship between parasites, hosts and the rhythms they both follow (Ellison et al, 2018(Ellison et al, , 2020. Considering the positive phototactic response of fish lice, aquaculture lights could attract lice to cages and facilitate infection (Trippel, 2010, Stewart et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent impact of these altered light regimes on both fish behaviour and health is now being considered. Recent studies have also found parasitic infection can alter host circadian gene expression, further complicating the relationship between parasites, hosts and the rhythms they both follow (Ellison et al, 2018(Ellison et al, , 2020. Considering the positive phototactic response of fish lice, aquaculture lights could attract lice to cages and facilitate infection (Trippel, 2010, Stewart et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Many fish, especially those in the ornamental trade, are transferred long distances to reach the end user and this movement also increases susceptibility and disease risk through mechanical disturbances 15 and reduced water quality from increased CO 2 and build‐up of other toxic compounds 16 . Within intensive aquaculture systems, water quality including dissolved oxygen levels are controlled, but stocking density is often pushed to its limit, which can also affect disease susceptibility 17,18 . For many species, high densities increase stress, as is the case with Atlantic salmon ( Salmo salar ) resulting in increased disease susceptibility 18 .…”
Section: Considerations When Selecting Aquatic Diagnosticsmentioning
confidence: 99%
“…16 Within intensive aquaculture systems, water quality including dissolved oxygen levels are controlled, but stocking density is often pushed to its limit, which can also affect disease susceptibility. 17,18 For many species, high densities increase stress, as is the case with Atlantic salmon (Salmo salar) resulting in increased disease susceptibility. 18 For territorial species, such as Nile tilapia (Oreochromis niloticus), high densities can lower stress, as social aggression is reduced 19 and consequently so too is disease susceptibility.…”
Section: Considerations When Selecting Aquatic Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, extreme lighting regimes may have profound implications for fish health and response to infection. Moreover, there are indications that infection and/or stress may impact expression of fish circadian clocks 34,35 .…”
Section: Introductionmentioning
confidence: 99%